Effect of Corporate Social Responsibility (CSR) and Compensation For Performance Management Manufacturing Companies Listed in Indonesia Stock Exchange Year 2014-2018 - Yosafat Gea; Haryetti Haryetti (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
In the midst of an increasingly modern business, requires companies to compete in maintaining their business and increase profits. Companies are also required not only for profit, but also improve the lives of the people, workers, stakeholders and gain confidence in the public eye. To achieve these objectives the company must pay attention to the company's performance and the factors that support the continuity of the company's performance. Corporate social responsibility and compensation management is an important aspect that should be viewed by the company to the sustainability of future performance. With the background of the problem, this study aims to examine the influence of corporate social responsibility and management compensation to company performance. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange 2014-2018 period as many as 153 companies with a total sample of 21 companies were selected based on criteria predetermined. The analytical method used in this research is multiple linear regression and the results show that corporate social responsibility is a significant positive effect on company performance and compensation management is not significant positive effect on company performance. The more disclosures made by the company in the annual report the company's performance is increasing.